Tafsir Ayat Ahkam dalam Perspektif Dilalah Manthuq dan Mafhum - Alex Kusmardani; Mohamad Athoilah; Mohamad Sar'an (CV. Syntax Corporation Indonesia, 2022)
Dilalah Manthuq and Mafhum have a very big influence in understanding the Qur'an. So a Mufassir must master it, its influence can make different interpretations. Without mastering dilalah manthuq and understanding, the interpretation will not be credible, it will not understand the text and textual. Understanding dilalah manthuq, and understanding can be evidence. In the study of Dilalah understanding and manthuq will affect the understanding of the verses of Al-Qur'an This study uses library research methods, namely research with reference to the book of interpretation, ulumul qur'an, ushul fiqh as primary sources and other books related to this research as secondary sources. In processing the data obtained from the literature, the authors use qualitative methods, in the form of inductive and deductive analysis. The purpose of this study is to find out the interpretation of the verse of al-Ahkam in terms of dilalah manthuq and mafhum. From the results of the study that Dilalah is something that can be used as a guide or an excuse. While the terminology means the appointment of a pronunciation to its meaning dilālah divided into manthuq and mafhum. Manthuq is divided into texts, zhahir, muawwal while mafhum is divided into mafhum muwafaqah and mafhum mukhalafah. Mafhum muwafaqah consists of two, namely lahn al-Khitab and fahwa al-Khitab. Meanwhile, the understanding of Mukhalafah consists of the understanding of al-Shifah, the understanding of al-ghayah, the understanding of conditions, the understanding of al-'adad, the understanding of al-laqab and the understanding of illat